2000
DOI: 10.1021/ja001271c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Hydrogenation of Heteroaromatic Compounds, Indoles

Abstract: Catalytic asymmetric hydrogenations of prochiral unsaturated compounds, 1 olefin, 2 ketone, 3 and imine, 4 have been intensively studied and are considered as a versatile method of creating a chiral carbon center. 5 However, no highly enantioselective hydrogenation of heteroaromatic groups has so far been reported except that of 2-methylquinoxaline to our knowledge. 6 Resonance stability of heteroaromatic compounds might impede the enantioselective hydrogenation, 7 which may find potentially wide applicability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
106
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(109 citation statements)
references
References 12 publications
0
106
0
3
Order By: Relevance
“…As reported by Ito, the addition of a base seems to be crucial in these hydrogenations. 8 Indeed, when 10 mol % of cesium carbonate was added to the hydrogenation of 1a, full conversion and ee's up to 74% were obtained (entries 3-7). Further experiments established that 40°C is optimal, pressure has no influence and other bases gave much poorer results.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As reported by Ito, the addition of a base seems to be crucial in these hydrogenations. 8 Indeed, when 10 mol % of cesium carbonate was added to the hydrogenation of 1a, full conversion and ee's up to 74% were obtained (entries 3-7). Further experiments established that 40°C is optimal, pressure has no influence and other bases gave much poorer results.…”
Section: Resultsmentioning
confidence: 98%
“…8 They found that the base has an important role in obtaining both good catalytic activity and enantioselectivity. Later, Kuwano et al reported the Rh-catalyzed asymmetric hydrogenation of N-tosyl-3-substitued indoles 9 and the Ru-catalyzed hydrogenation of N-protected-2-and 3-substituted indoles with excellent enantioselectivities and conversions using the same Ph-TRAP ligand.…”
mentioning
confidence: 99%
“…It produces an important, particularly for catalyst based on 4a, increase in conversion, although racemic products were unexpectedly obtained (entries 8-10). [18][19] It is noteworthy that catalysts with different phosphine groups and dynamic properties give null enantioselectivity, pointing to a general effect of the additive. It looks therefore apparent that the addition of base leads to an alternative catalyst.…”
Section: Rc(o)mentioning
confidence: 99%
“…5,6 Dearomatization reaction of indoles is a powerful and attractive approach for the direct preparation of indoline derivatives, which has been extensively studied over the past decade. 710 Recently, we reported the first CB bond-forming dearomatization of indoles using a chiral copper(I) catalyst to give the corresponding optically active 3-borylindolines.…”
mentioning
confidence: 99%